PENATALAKSANAAN PEMERIKSAAN FISIK VITAL SIGNS PADA PASIEN SAAT MASA PANDEMI COVID-19 - Ibrahim, Ibrahim; Anjani, Arum Dwi; Santi, Yollanda Dwi; Diana, Sharifah; Sitompul, Jekson (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
This outbreak was caused by the emergence of a new virus finding called the corona virus or it could also be called Corona Virus Disease 2019 (COVID-19) which is an outbreak of a disease that is transmitted through the respiratory tract caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV- 2). This disease outbreak spreads widely throughout the world in just a short time, this can happen because when someone touches items that have been contaminated by other people, after that the virus can move to the nose, eyes, mouth through contaminated items.Therefore, during the current corona virus pandemic, it is very necessary to have the most basic physical examination, namely the examination of vital signs or also called vital signs that must be carried out on every individual.The basic physical examination aims to determine the patient's health condition and when carrying out a physical examination in the midst of the Covid-19 disease outbreak, it must be carried out according to the procedure in the midst of the Covid-19 virus pandemic because during this pandemic period it takes a long time to serve patients, this is due to the number of patients.